Agricultural production in Tajikistan: Evidence from twelve districts in Khatlon Province, 2015–2023 - Lambrecht, Isabel B.; Pechtl, Sarah; Aliev, Jovidon; Akramov, Kamiljon T.; Khakimov, Parviz (International Food Policy Research Institute, 2023)
Survey data from 2000 households in 12 districts of Khatlon Province, USAID’s Zone of Influence (ZOI), were analyzed to document changes in the agriculture sector between 2015 and 2023. Key findings • Participation in agriculture remained constant at 85 percent of households, yet the average cultivated area significantly decreased from 2015 to 2023, likely due to the parallel increase in the number of households in the study area as well as the further division of dehkan farms. • Cropping patterns have changed since 2015. Among others, we find a stark increase in cultivation of maize, whereas cotton is grown at similar frequency but on a significantly smaller average plot area. Overall, we observe a positive increase in the diversity of (semi-)annual crops. • Mechanization is used for land preparation of plots for nearly all major crops now, up from much lower levels in 2015. Mechanization for harvesting significantly increased on plots with fodder crops (from 6 percent to 15 percent) and maize plots (from 2 percent to 8 percent). Most households rely on rental services as few own the needed machinery. • More households have water pumps, greenhouses, and cold storage, and more household and presidential plots having irrigation in 2023 than in 2015. Agricultural innovations including drip irrigation and solar panels also emerge but are still implemented at very low levels (<1 percent). • Cattle ownership declined from 2015 to 2023 and, accordingly, fewer households have cows producing milk (40 percent vs. 33 percent). This may—at least partly—explain the lower rates of dairy consumption observed among female respondents in 2023. • Poultry ownership increased dramatically (from 7 percent to 25 percent) and is now owned at similar rates across different types of households, including more vulnerable or disadvantaged households. Accordingly, there is more household-level consumption of eggs in the survey area.